EXTH-09. NEO-ADJUVANT TEMOZOLOMIDE INCREASES THE EFFICACY OF SUBSEQUENT CONCURRENT CHEMORADIATION IN A TRANSGLUTAMINASE-2 DEPENDENT MANNER. (9th November 2020) - Daniel, Paul; Meehan, Brian; Sabri, Siham; Shenouda, George; Sarkaria, Jann; Rak, Janusz; Abdulkarim, Bassam
Abstract: Glioblastoma (GBM) is invariably fatal due to failure of current chemoradiation (Stupp) regimes. Biomarkers such as MGMT have proven to predict response to Temozolomide (TMZ). An equivalent biomarker for radiation (RT) has not yet been identified. Transglutaminase-2 (TGM2) has been implicated in driving radiation resistance; but the mechanism is poorly understood. We have investigated how exposure to neoadjuvant TMZ in glioma stem cells (GSCs) with different levels of TGM2 would affect the response to RT. MATERIALS/METHODS: Primary GSCs lines with different TGM2 levels (high: 1123, 83; low: 528, OPK49) were used to explore the role of TGM2 in RT response and modulation of expression by TMZ in vitro and in-vivo. RESULTS: We showed that TGM2 drives radioresistance in GSCs through restriction of p53 mediated repression of RAD51 expression. We demonstrate that exposure of GSCs to TMZ drives rapid downregulation of TGM2 in vitro and this phenomenon is recapitulated in vivo . Interestingly, we confirm that RT is able to drive reciprocal changes in TGM2 and promotes reactivation of TGM2 in TGM2-high tumours but not TGM2-low tumours. Given these observations, we hypothesized that exposure to neoadjuvant TMZ in TGM2-low tumours would increase the efficacy of subsequent RT in these tumours. Comparison of the effect of standard treatment consisting of 3 weeks of concurrent TMZ and RT (Stupp) to a novel regime (neo-Stupp) consisting of 1 week of neoadjuvant TMZ followed by two weeks of TMZ and hypofractionated RT revealed a superior survival benefit of this novel regime in TGM2-low tumours but not in TGM2-high tumours. Utilization of the TGM2 inhibitor GK921 in combination with neo-Stupp prevented rapid relapse previously observed in TGM2-high tumours. CONCLUSION: We provide evidence that TGM2 is a biomarker of RT response and can be used to tailor chemoradiation protocols to the unique biology of each individual GBM patient.